Trajectory of Cognitive Decline After Incident Heart Failure Hospitalization: Findings From the REGARDS Study - Madeline R. Sterling; Joanna Bryan Ringel; Monika M. Safford; Parag Goyal; Yulia Khodneva; Leslie A. McClure; Raegan W. Durant; Alexandra E. Jacob; Emily B. Levitan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cognitive impairment is common among adults with heart failure (HF) and associated with poor outcomes. However, less is known about the trajectory of cognitive decline after a first HF hospitalization. We examined the rate of cognitive decline among adults with incident HF hospitalization compared with those without HF hospitalization. Methods and Results The REGARDS (Reasons for Geographic and Racial Differences in Stroke) study is a prospective longitudinal study of 23 894 participants aged ≥45 years free of HF at baseline. HF hospitalization was expert adjudicated. Changes in global cognitive function (primary outcome) were assessed with the Six‐Item Screener (range, 0–6). Secondary outcomes included change in Word List Learning (range, 0–30), Word List Delayed Recall (WLD; range, 0–10), and Animal Fluency Test (range, 0+). Segmented linear mixed‐effects regression models were used. Over 5 years, mean scores across all 4 cognitive tests declined for all participants regardless of HF status. Those with incident HF hospitalization experienced faster declines in the Six‐Item Screener versus those who were HF free (difference, −0.031 [95% CI, −0.047 to −0.016]; P<0.001), a finding that persisted in fully adjusted models. Those with incident HF hospitalization did not experience faster declines in Word List Learning, Word List Delayed Recall, or Animal Fluency Test scores compared with those without HF hospitalization. Participants with hospitalization for HF with preserved, compared with reduced, ejection fraction had faster decline in Animal Fluency Test. Conclusions Global cognitive decline occurred faster among adults with incident HF hospitalization compared with those who remained free of HF hospitalization. This pattern was not seen for the other cognitive domains.